Bronze Age settlement mounds on the Colchian plain at the Black Sea coast of Georgia: A geoarchaeological perspective. Issue 4 (7th December 2017) - Laermanns, Hannes; Kirkitadze, Giorgi; May, Simon Matthias; Kelterbaum, Daniel; Opitz, Stephan; Heisterkamp, Arne; Basilaia, Giorgi; Elashvili, Mikheil; Brückner, Helmut
Abstract: Situated between the Enguri and Khobistskali rivers, more than 30 settlement mounds (locally named Dikhagudzuba ) provide evidence for a relatively densely populated landscape in the coastal lowlands of western Georgia during the Bronze Age. Compared to older mounds in eastern Georgia and other regions, these mounds differ not only in age but also in their average size and spatial distribution. Based on the interpretation of nine sediment cores, drone survey and structure‐from‐motion photogrammetry techniques, our study aims at (i) establishing a chronostratigraphic framework for the mounds based on 14 C dating; (ii) reconstructing possible phases and gaps in human occupation; (iii) determining potential source areas of the mounds' construction material; and (iv) identifying the environmental conditions at the time of their use. The three investigated mounds are similar in dimension and stratigraphy. Anthropogenic layers could clearly be identified and separated from the natural alluvial deposits below. According to the 14 C age estimates, the mounds date to the first half of the 2nd millennium B.C.; this confirms the archaeological interpretation of their Bronze Age origin. While only one construction phase is assumed for two of the mounds, stratigraphic analysis suggests a successive enlargement of a third mound over at least 470 years. Paleoenvironmental conditions in the vicinity of the mounds were dominated by swampy, fluvial (channel) to alluvial (overbank) processes, as attested by river‐bank deposits and floodplain alluvium.